When Artists Fall: Honoring and Admiring the Immoral - Archer, Alfred; Matheson, Benjamin (Journal of the American Philosophical Association, 2019)
Is it appropriate to honor artists who have created great works but who have also acted immorally? In this article, after arguing that honoring involves identifying a person as someone we ought to admire, we present three moral reasons against honoring immoral artists. First, we argue that honoring can serve to condone their behavior, through the mediums of emotional prioritization and exemplar identification. Second, we argue that honoring immoral artists can generate undue epistemic credibility for the artists, which can lead to an indirect form of testimonial injustice for the artists’ victims. Third, we argue, building on the first two reasons, that honoring immoral artists can also serve to silence their victims. We end by considering how we might respond to these reasons.
Keywords: Bibliographie

Sex Worker Resistance in the Neoliberal Creative City: An auto/ethnography - Tigchelaar, Alex (Anti-Trafficking Review, 2019)
Sex workers are subjects of intrigue in urban and creative economies. Tours of active, deteriorating, or defunct red-light districts draw thousands of tourists every year in multiple municipalities around the world. When cities celebrate significant anniversaries in their histories, local sex worker narratives are often included in arts-based public offerings. When sex workers take up urban space in their day-to-day lives, however, they are criminalised. Urban developers often view sex workers as existing serviceably only as legend. A history of sex work will add allure to an up-and-coming neighbourhood, lending purpose to its reformation into a more appropriately productive space, but the material presence of sex workers in these neighbourhoods is seen as a threat to community wellbeing and property values. This paper considers how sex workers, continuously displaced from environments they have carved out as workspaces, may use the arts to draw attention to these ongoing contradictions. It investigates how sex workers may make visible the idiosyncratic state of providing vitality to a city’s history while simultaneously being excluded from its living present. Most critically, it suggests ways in which sex workers may encourage those involved as producers and consumers of neoliberal urban revitalisation projects to connect these often fatal paradoxes to the laws that criminalise their labour.
Keywords: Bibliographie; Nettoyer

Comment écrire le viol ? - Clément, Éric (La Presse+, 2018)
Le sujet est délicat. Tellement que plusieurs personnes contactées ont refusé de se prononcer sur cette nouvelle prise de conscience qui découle des mouvements #moiaussi et #agressionnondénoncée. Les romanciers doivent-ils s’autocensurer pour respecter une nou
Keywords: Bibliographie; Nettoyer

Code of Silence: A call to action to address and prevent abuse in dance communities - Forcier, Marie France (The Dance Current, 2017)
Keywords: Bibliographie; Nettoyer

Agression sexuelle : L'écrivain Maxime Roussy remis en liberté - Helmlinger, Julien (ActuaLitté, 2013)
Keywords: Bibliographie; Nettoyer

Sexual Harassment and Violence at Music Concerts and Festivals - Heen, Miliaikeala Sj.; Lieberman, Joel D. (Center for Crime and Justice Policy, 2018)
Publisher: 6876
Keywords: Bibliographie; Nettoyer

intersectionnalité - Office québécois de la langue française (Grand dictionnaire terminologique, 2019)
Cumul de différentes formes de domination ou de discrimination vécues par une personne, fondées notamment sur sa race, son sexe, son âge, sa religion, son orientation sexuelle, sa classe sociale ou ses capacités physiques, qui entraîne une augmentation des préjudices subis.
Keywords: Bibliographie; Nettoyer

Université de Montréal: briser l'omerta - Elkouri, Rima (La Presse, 2018)
Keywords: Bibliographie; Nettoyer

Représentation du viol en littérature: pour dire quoi? - Boisclair, Isabelle (Le Devoir, 2018)
Keywords: Bibliographie; Nettoyer

Danse #WeToo - Ferron, Geneviève C. (Regroupement québécois de la danse, 2018)
// English version Depuis l’émergence du mouvement #metoo en octobre dernier, plusieurs femmes artistes du Québec ont pris la parole pour dénoncer le harcèlement, l’intimidation et les abus dont elles ont été victimes ou témoins dans le cadre de leur […]
Keywords: Bibliographie; Nettoyer

Consultations publiques sur le harcèlement et la violence sexuelle en milieu de travail: ce que nous avons entendu - Emploi et Développpement social Canada (Gouvernement du Canada, 2017)
OCLC: 1015238443
Keywords: Bibliographie; Nettoyer

Une victime de Claude Jutra témoigne: des attouchements dès 6 ans - Pilon-Larose, Hugo (La Presse, 2016)
Keywords: Bibliographie; Nettoyer

Jian Ghomeshi est acquitté - Radio-Canada (Radio-Canada, 2016)
Jian Ghomeshi est acquitté de toutes les accusations qui pesaient contre lui. Le juge William B. Horkins a rendu sa décision, jeudi matin, à Toronto.
Publisher: Radio-Canada.ca
Keywords: Bibliographie; Nettoyer

Comment aider un·e ami·e qui a eu des comportements abusifs par le passé (et qui a changé depuis) ? - Thom, Kai Cheng (Nous faire justice : Reader sur le viol et les ripostes extra-pénales, 2019)
Keywords: Bibliographie; Dans le rapport; Nettoyer

Orchestres symphoniques: une parité favorisée par un processus à l'aveugle - Larochelle, Samuel (La Presse, 2018)
Femmes et hommes côte à côte dans les orchestres symphonique d'ici. La question de parité est souvent lié au processus de sélection à l'aveugle des musiciens, une façon de faire qui permet de mettre de l'avant le talent, et ce, peu importe le sexe des artistes.
Keywords: Bibliographie; Nettoyer

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
This article contextualizes some of the roles that women played in Montreal’s interwar jazz scene. The archives testify to the importance of pianists such as Vera Guilaroff and Ilene Bourne, piano teacher Daisy Peterson Sweeney, dance teachers Olga Spencer Foderingham and Ethel Bruneau, as well as black women performers on the variety stage in the development of Canada’s most thriving jazz scene in the first half of the twentieth century. This article explains why women were drawn to these particular performance spaces (piano, teaching, theatrical dance) and documents the historiographical processes that have led to their marginalization from the historical record.
Publisher: Société québécoise de recherche en musique
Keywords: Bibliographie; Nettoyer

Not in our house Chicago Theatre Community (Not in our house Chicago Theatre Community, 2017)
making safe spaces to do dangerous work
Keywords: Bibliographie; Nettoyer

Rhetorical Constellations and the Inventional/Intersectional Possibilities of #MeToo - Bloomfield, Emma Frances (Journal of Communication Inquiry, 2019)
Publisher: SAGE Publications Inc
Keywords: Bibliographie; Nettoyer

900 000 $ pour contrer les agressions sexuelles et le harcèlement dans le milieu culturel québécois - Ministère de la Culture et des Communications (Gouvernement du Québec, 2018)
Keywords: Bibliographie; Nettoyer

Attouchements sexuels sur une élève : Romuald Pavy plaide coupable (Radio-Canada, 2011)
Le professeur de danse Romuald Pavy a plaidé coupable mardi matin à des accusations d'attouchements sexuels sur l'une de ses élèves.
Publisher: Radio-Canada.ca
Keywords: Bibliographie; Nettoyer

Le harcèlement en milieu de travail au Québec - Conseil des ressources humaines du secteur culturel (YouTube, 2019)
Conseil des ressources humaines du secteur culturel
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Harcèlement en milieu de travail dans les arts : à l’intention des travailleurs culturels - Conseil des ressources humaines du secteur culturel (YouTube, 2019)
Conseil des ressources humaines du secteur culturel
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Harcèlement en milieu de travail dans les arts : à l'intention des employeurs (YouTube, 2019)
Conseil des ressources humaines du secteur culturel
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Trousse à outil pour la gestion des ressources humaines : Harcèlement et violence dans le milieu de travail - Conseil des ressources humaines du secteur culturel. (2019)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

LGBT People and the UK Cultural Sector: The Response of Libraries, Museums, Archives and Heritage since 1950 - Vincent, John (Routledge, 2016)
This book examines the complex and conflicting relationships between LGBT people and our cultural and heritage organisations including libraries, museums and
Keywords: Bibliographie; Nettoyer

Negotiating the gay male stereotype in ballet and modern dance - Polasek, Katherine M.; Roper, Emily A. (Research in Dance Education, 2011)
Dance, ballet and modern in particular, is culturally defined as a feminine activity in the United States. The purpose of the present study was to examine the experiences of professional male modern and ballet dancers in the United States. Semi-structured interviews were conducted with 12 current professional ballet and modern dancers. We examined the ways in which the dancers initially became involved in dance, any support or opposition they may have confronted, and the ways in which they negotiated the stereotypical assumptions surrounding men’s involvement in dance. Four emergent themes are discussed: (1) exposure to and entrance into dance; (2) the gay stereotype; (3) negotiating the gay stereotype; and (4) homophobia within the dance community. The social significance of this study is rooted in the ways in which our culture constructs gender, the body, and movement, restricting both males and females from using and exploring their bodies in ways not deemed gender-appropriate. Attention is also given to the ways in which we can create and nurture meaningful experiences for a greater number of individuals.
Keywords: Bibliographie; Nettoyer; gay men; homophobia; male dancers; masculinity

“A Different Kind of Man”: Mediated Transgendered Subjectivity, Chaz Bono on Dancing With the Stars - Mocarski, Richard; Butler, Sim; Emmons, Betsy; Smallwood, Rachael (Journal of Communication Inquiry, 2013)
Chaz Bono’s appearance on Dancing with the Stars (DWTS) marks one of the first primetime, network appearances of a postoperative transgender person. This article deconstructs the mediated gender subjectivities of Bono as constructed by the show itself via prerecorded segments, costume and song choices, dance partner interaction, and judges’ commentaries as well as those projected by Bono during the live, unscripted portions of the show. Combining notions of the normalization of taboo sexual subjectivities through mediated contexts with lens of gender performativity, we demonstrate how transgender subjectivities are presented to a mainstream audience via such mediated choices, but also how Bono welds some agency to resist such normalization through his live performances. Bono’s appearance on DWTS stands as an important step toward acceptance of transgendered persons in mainstream society, however through a neutered, sex-free rhetoric as projected by the mediated portions of the show, his appearance is not without controversy. Additionally, we posit that Bono represents a transnormativity of a White, upper-class postoperative heterosexual male, which others all transgendered persons who fall outside of those hegemonic parallels of safe subjectivities.
Keywords: Bibliographie; Nettoyer

LGBTQ Welcoming Guidelines for Museums: developing a resource for the museum field - Leitch, Christopher; Youngs, Renae; Gavigan, Annette; Lesperance, Michael; Burns, William James; Cohen-Stratyner, Barbara; Hammond, Paul; Hansen, Jaden (Museums & Social Issues, 2016)
Beginning in 2014, the LGBTQ Alliance professional network of the American Alliance of Museums (AAM) met to develop and publish a broad set of LGBTQ Welcoming Guidelines for Museums. The authors sought to help museums be more inclusive of lesbian, gay, bisexual, transgender and queer staff and visitors. The Guidelines conform to the most recent established standards of professional practice in museums and touch on all areas of museum work; they may be viewed as part informational reference, part institutional self-assessment tool. The Guidelines were unveiled at the AAM’s 2016 annual meeting, and are now available at no charge online (http://www.aam-us.org/resources/professional-networks/lgbtq). The LGBTQ Alliance encourages readers to use and review the Guidelines and to make observations, critiques and corrections directly to the current chair, Mike Lesperance (mike@thedesignminds.com).
Publisher: Routledge _eprint: https://doi.org/10.1080/15596893.2016.1217460
Keywords: Bibliographie; Coffre à outils; Lesbian; Nettoyer; bisexual; diversity; gay; inclusion; transgender

More Than Two-Spirit: Queer Indigenous Sovereignty and Survivance in Museums - Cooper, Caitlin Skye (Université de Washington, 2017)
Keywords: Bibliographie; Nettoyer

What Makes a Lesbian Salsa Space Comfortable? Reconceptualising Safety and Homophobia - Boulila, Stefanie Claudine (Lesbian Geographies: Gender, place and power, 2015)
This chapter explores the sexual spatialisation of salsa dance spaces through the narratives of lesbian salsa dancers. It draws on conversations with seven
Num Pages: 20
Keywords: Bibliographie; Nettoyer

Le traitement médiatique du mouvement #AgressionNonDénoncée dans la presse écrite québécoise francophone - Savard-Moisan, Raphaëlle (Université du Québec à Montréal, 2017)
Keywords: Bibliographie; Nettoyer

Michel Brûlé visé par une plainte d'agression sexuelle à Québec - Piedboeuf, Guillaume (La Tribune, 2017)
Une écrivaine de la Rive-Sud de Québec accuse l’éditeur Michel Brûlé de l’avoir agressée sexuellement à sa résidence du Vieux-Québec, en mars 2014, alors qu’elle venait lui proposer un manuscrit. Jill Côté a porté plainte à la police de Québec, vendredi, pour un incident dont M. Brûlé nie l’existence.
Keywords: Bibliographie; Nettoyer

L'écrivain jeunesse Maxime Roussy en prison pour 5 ans - Nguyen, Michael (Le Journal de Montréal, 2017)
Pendant cinq ans, de 2006 à 2011, Roussy avait profité d’une jeune lectrice pour assouvir ses fantasmes sadomasochistes.
Keywords: Bibliographie; Nettoyer

Les abus et la «loi du silence» dans la danse - Morneau, Caroline (Le Journal de Québec, 2019)
Abus psychologiques, physiques, sexuels: après les milieux du cinéma et de l’humour, on réalise que celui de la danse comporte son lot de scandales.
Keywords: Bibliographie; Nettoyer

Le patron des Éditions des Intouchables Michel Brûlé à son tour visé par des allégations d’inconduites sexuelles - Lévesque, Ève (Le Journal de Montréal, 2017)
Sept ex-employées se vident le cœur.
Keywords: Bibliographie; Nettoyer

Le #moiaussi de la danse - Lauzon, Véronique (2019)
Des acteurs du milieu de la danse brisent le silence sur les abus de pouvoir, le harcèlement psychologique et les agressions sexuelles vécus. Deux ans après #moiaussi, une quinzaine d’entre eux tentent de faire éclater l’omerta qui plombe cet environnement jugé toxique.
Keywords: Bibliographie; Nettoyer

Des musiciennes unies contre le sexisme - Lauzon, Véronique (La Presse, 2017)
Cent trente-cinq femmes issues du milieu musical ont décidé de dénoncer le sexisme et les injustices qu'elles subissent régulièrement au travail.
Keywords: Bibliographie; Nettoyer

« Sous la ceinture, unies pour vaincre la culture du viol », un livre qui tombe à point - Radio-Canada (Radio-Canada, 2016)
Judith Lussier, l'une des auteurs du livre « Sous la ceinture, unis pour vaincre la culture du viol », souligne que ce phénomène est omniprésent et tend à banaliser les gestes des agresseurs.
Publisher: Radio-Canada.ca
Keywords: Bibliographie; Nettoyer

Ghomeshi, l’avant et l’après - Deglise, Fabien (Le Devoir, 2014)
L’ex-animateur-vedette emporte aussi dans sa chute la loi du silence envers les abus sexuels.
Keywords: Bibliographie; Nettoyer

«Sous la ceinture»: La culture du viol, «pas une lubie de féministe» - Chabot, Kim (HuffPost, 2016)
«Sous la ceinture»: La culture du viol, «pas une lubie de féministe»
Keywords: Bibliographie; Nettoyer

Sexisme en danse : le mur du silence s’effrite au Québec - Carpentier, Mélanie (Jeu : revue de théâtre, 2018)
Un article de la revue Jeu, diffusée par la plateforme Érudit.
Publisher: Cahiers de théâtre Jeu inc.
Keywords: Bibliographie; Nettoyer

Une nouvelle décrivant un viol entraîne la démission de la directrice de la revue «XYZ» - Caillou, Annabelle (Le Devoir, 2018)
Vanessa Courville a claqué la porte de la revue consacrée à la nouvelle littéraire.
Keywords: Bibliographie; Nettoyer

Comment parler des violences faites aux femmes en littérature? - Caillou, Annabelle (Le Devoir, 2018)
Trois spécialistes se penchent sur le sujet. Analyse.
Keywords: Bibliographie; Nettoyer

Léa Clermont-Dion accuse Michel Venne de l’avoir agressée - Bussières, Ian; Piedboeuf, Guillaume (Le Soleil, 2017)
L’écrivaine et militante Léa Clermont-Dion, qui avait révélé en 2014 avoir été agressée sexuellement à l’âge de 17 ans, a déposé une plainte à la police contre le fondateur de l’Institut du Nouveau Monde, Michel Venne. Des allégations d’agression sexuelle que nie ce dernier.
Keywords: Bibliographie; Nettoyer

Mesures de soutien et d’inclusion des personnes trans et des personnes non binaires en milieu de travail : Guide pour les employeurs et les syndicats - Table nationale de lutte contre l'homophobie et la transphobie des réseaux de l'éducation (2019)
Keywords: Bibliographie; Nettoyer

Modèle de politique pour la création d'un milieu de travail sain, respectueux et exempt de discrimination, de harcèlement et de violence - Labine, Lise; Lorquet, Me Sébastien (L’Association des théâtres francophones du Canada, 2018)
L’Association des théâtres francophones du Canada a développé ce modèle de politique pour ses compagnies membres avec l’appui de Théâtre Action.
Keywords: Bibliographie; Nettoyer

Formation sur le respect en milieu du travail (2019)
Cette session d’information au sujet de milieux de travail respectueux explore les raisons derrière l’augmentation du nombre de problèmes de comportement en milieu de travail, de son impact, ainsi que de l'importance de définir les attentes en matière de comportement afin d'aider les employeurs et les organismes à gérer, contrôler et prévenir les comportements pouvant constituer du harcèlement (harcèlement sexuel, discrimination, intimidation et violence ).
Keywords: Bibliographie; Nettoyer

Our Music My Body: 2017 Campaign & Survey Report - OurMusicMyBody (2017)
Keywords: Bibliographie; Nettoyer

Intégrer les personnes trans en milieu de travail - Fondation émergence; Aide aux Trans du Québec (ATQ) (2018)
Keywords: Bibliographie; Nettoyer

Code de Conduite pour les arts de la scène au Canada - Milieux de travail respectueux dans les arts (2019)
Keywords: Bibliographie; Dans le rapport; Nettoyer

Code de conduite - Industries créatrices du Canada (lirelecode.ca, 2018)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Debranchée (Unplugged) - Laurier, Mathilde; St-Laurent, Marie-Claude; Hébert, Maude; Milot, Marie-Ève (2017)
Débranchée (Unplugged) est une fiction qui traite des violences sexuelles dans le monde adolescent. La pièce raconte l'histoire de deux amies ébranlées par les rumeurs d'agressions sexuelles qui se propagent à haute vitesse dans leur école. Quand Allison brise la loi du silence, toute une chaîne de réactions s'enclenche. Des témoignages fusent, donnant une voix à toutes ces violences sexuelles trop souvent vécues dans l'anonymat. Devant l'ampleur du phénomène, les deux protagonistes cherchent à transformer l'explosion créée en un élan de solidarité. Elles iront jusqu'au bout. Le show aura lieu.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Allégations de nature sexuelle: Gilbert Rozon visé par neuf femmes - Pineda, Améli (Le Devoir, 2017)
Neuf femmes racontent au «Devoir» ainsi qu’au 98,5 FM avoir été victimes de harcèlement et d’agressions sexuelles de la part du fondateur de Juste pour rire, Gilbert Rozon, et ce, dans la foulée du mouvement #MeToo. Certaines d'entre elles étaient même mineures au moment des incidents rapportés. Et pendant des années, elles ont cru être seules.
Keywords: Bibliographie; Nettoyer

Inconduites sexuelles reprochées à Éric Salvail - Gagnon, Katia; Vallet, Stéphanie (La Presse, 2017)
Avances sexuelles en string, parties intimes exhibées ou empoignées, tentatives de séduction insistantes dans des salles de montage: 11 personnes ont raconté à La Presse avoir subi des inconduites, ou en avoir été témoins, de la part du producteur et animateur Éric Salvail, la plupart du temps dans un contexte professionnel.
Keywords: Bibliographie; Nettoyer

From victim to survivor - and from survivor to victim: Reconceptualising the survivor journey - Jordan, Jan (Sexual Abuse in Australia and New Zealand, 2013)
Being recognized as a rape survivor has often been interpreted as implying a linear progression from the negative state of victimisation, experienced in the presence of the offender, to a stronger, more positive state, typically facilitated by external support mechanisms. Drawing primarily on interviews conducted with women victimised by New Zealand serial rapist, Malcolm Rewa, this article challenges the concept of a journey 'from victim to survivor' by considering the multiple ways in which these women sought to protect themselves and survive during the attack while also experiencing aspects of their postattack involvement with individuals and agencies as further victimisation. The article concludes by outlining some initial implications regarding what this may mean for professionals working with victim/survivors of sexual violence.
Publisher: Australian and New Zealand Association for the Treatment of Sexual Abuse
Keywords: Bibliographie; Nettoyer

Le respect de la dignité des femmes dévoilant une agression à caractère sexuel:perspectives d'intervenantes sociales et communautaires Montréalaises - Souffrant, Kharoll-Ann (Université McGill, 2019)
Publisher: McGill University
Keywords: Bibliographie; Nettoyer

Un enseignant de l'École nationale de cirque accusé de crimes sexuels - Radio-Canada (Radio-Canada, 2018)
L'entraîneur Marcelo Berti Marques fait face à quatre chefs d'accusation, entre autres pour avoir envoyé une photo de ses organes génitaux à un de ses anciens élèves de l'École nationale de cirque, à Montréal. Sa présumée victime est soulagée, mais craint qu'il ait fait d'autres victimes.
Keywords: Bibliographie; Nettoyer

*Loi visant à prévenir et à combattre les violences à caractère sexuel dans les établissements d’enseignement supérieur - Gouvernement du Québec (2017)
Keywords: Bibliographie; Nettoyer

The Morality of Musical Men: From Victorian Propriety to the Era of #MeToo - Shaver-Gleason, Linda (2018)
Keywords: Bibliographie; Nettoyer

Workplace Sexual Harassment 30 Years on: A Review of the Literature - McDonald, Paula (International Journal of Management Reviews, 2012)
Despite its proscription in legal jurisdictions around the world, workplace sexual harassment (SH) continues to be experienced by many women and some men in a variety of organizational settings. The aims of this review article are threefold: first, with a focus on workplace SH as it pertains to management and organizations, to synthesize the accumulated state of knowledge in the field; second, to evaluate this evidence, highlighting competing perspectives; and third, to canvass areas in need of further investigation. Variously ascribed through individual (psychological or legal consciousness) frameworks, sociocultural explanations and organizational perspectives, research consistently demonstrates that, like other forms of sexual violence, individuals who experience workplace SH suffer significant psychological, health- and job-related consequences. Yet they often do not make formal complaints through internal organizational procedures or to outside bodies. Laws, structural reforms and policy initiatives have had some success in raising awareness of the problem and have shaped rules and norms in the employment context. However, there is an imperative to target further workplace actions to effectively prevent and respond to SH.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1468-2370.2011.00300.x
Keywords: Bibliographie; Nettoyer

L'Union des artistes dépose des griefs pour harcèlement - Radio-Canada (Radio-Canada, 2017)
Après une vague de dénonciations de gestes à caractère sexuel dans le milieu artistique, l'Union des artistes (UDA) annonce avoir déposé des griefs pour harcèlement.
Keywords: Bibliographie; Nettoyer

Musical genius and/or nasty piece of work? Dealing with violence and sexual assault in accounts of popular music’s past - Strong, Catherine; Rush, Emma (Continuum, 2018)
For many years, the mistreatment of women in particular has essentially been normalized in many parts of the music industry. In recent years, however, there has been an increase in women coming forward and telling their stories, and asking that men be held accountable for wrongdoing. This interdisciplinary (sociology and philosophy) paper pursues two key feminist questions prompted by recent developments. Firstly: How has the construction of the history of popular music legitimated the continuation of this situation? ‘Looking back’ historically and sociologically, examples are provided of the legitimation or ignoring of violence against women (VAW) in the history of popular music to date. Secondly: How should we [archivists, historians, heritage curators and popular music educators], from now on, construct the history of popular music in a way that doesn’t legitimate VAW? Turning to ‘look forward’, applied ethics frameworks are used to explore different aspects of this second question.
Keywords: Bibliographie; Nettoyer

Les dénonciations publiques d'agressions sexuelles : du mauvais usage de la présomption d’innocence - Lessard, Michaël (Revue Femmes et Droit, 2017)
French Abstract: Lorsqu’une victime dénonce son agresseur sur la place publique, certaines personnes tentent de la réduire au silence en invoquant le droit à la présomption d’innocence. Ce fut particulièrement évident en 2014, lors du mouvement #AgressionNonDénoncée ; ce le fut encore à l’automne 2015, alors que des femmes autochtones de Val-d’Or dénonçaient les agressions sexuelles commises à leur endroit par des policiers ; ce le fut aussi en 2016 à l’occasion de la dénonciation du député Gerry Sklavounos par Alice Paquet ; et l’argument légaliste réapparaît ainsi périodiquement sur la scène publique. Pourtant, peut-on vraiment bâillonner une victime en mettant de l’avant les droits de son agresseur ? L’auteur estime qu’il s’agit là d’un mauvais usage de la présomption d’innocence. Dans ce texte, il explique que la présomption d’innocence doit être replacée dans son contexte juridique. Le droit à la présomption d’innocence est un principe fondamental qui protège les accusés contre le pouvoir punitif de l’État. Il trouve uniquement application dans le processus pénal et n’est pas conçu pour être employé sur la scène publique. De plus, l’auteur explique que, dans le cadre du processus pénal, la présomption d’innocence favorise la création d’un espace de discussion où les parties peuvent débattre de la culpabilité. Pourtant, lorsqu’elle est invoquée sur la scène publique, elle ne fait que placer les victimes dans un processus violent de remise en question de leur crédibilité, tout en protégeant les agresseurs. Son invocation crée une atmosphère qui décourage les dénonciations. Le débat public dévie, laissant peu de place pour critiquer nos systèmes de plaintes dysfonctionnels et la culture du viol. En ce sens, la présomption d’innocence n’est pas invoquée afin d’établir un dialogue constructif, mais plutôt pour faire taire les critiques.English Abstract: When a victim reports her aggressor publicly, some people try to silence her voice under the guise of the right to the presumption of innocence. This was especially remarkable in 2014, within the movement #AgressionNonDénoncée; and again in the fall of 2015, when Val-d’Or Indigenous women reported being sexually assaulted by police. It was also the case in 2016 when Alice Paquet denounced Member of Provincial Parliament Gerry Sklavounos, and the legal argument thus periodically reappears on the public stage. However, can we really silence a victim by advancing the rights of her aggressor? The author believes that this is a case of inappropriate use of the presumption of innocence. In this text, he explains that the presumption of innocence must be placed in its legal context. The right to the presumption of innocence is a principle that protects litigants against the punitive power of the state. Its sole application belongs in the criminal process, and it was not designed to be used as such on the public stage. In addition, the author explains that, at the heart of the criminal process, the presumption of innocence promotes the creation of a discussion space where all parties may debate the guilt. However, when it is invoked in the public sphere, it only places the victims in an aggressive process of questioning their credibility while protecting the aggressors. Its invocation creates a climate that deters denunciations of sexual assaults. The public debate deviates, leaving little room to criticize our dysfunctional complaint systems and rape culture. In that sense, the presumption of innocence is not invoked in order to establish a constructive dialogue, but it has the effect of shutting down its critics. In this article, the author explains why the right to the presumption of innocence must not be engaged in this way in the public sphere.
Keywords: Bibliographie; Nettoyer

Encouraging Safer and More Supportive Working Practices in Theatre - Society of London Theatre; UK Theatre (2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Education in Theatrical Intimacy as Ethical Practice for University Theatre - Shawyer, Susanne; Shively, Kim (Journal of Dramatic Theory and Criticism, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël; acting; ethics; pedagogy; theatre; theatrical intimacy

Masculinity after #MeToo in Mainstream Theatre - Mignon, Eloïse; Rae, Paul (Performance Research, 2019)
Keywords: #MeToo; Arthur Miller; Bibliographie; Geoffrey Rush; King Lear; Nettoyer; Raphaël; Sarah Kane; masculinity; theatre

Performing Arts Training in the Age of #MeToo - Spencer, Jennifer (Voice and Speech Review, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Institutional Responses to #MeToo: A Conversation - Mengesha, Weyni; Dreyer-Lude, Melanie; Clarke, Kristian; Shaw, Kathryn; Warwick, Jacqueline; Palmer, Alisa; Dubois, Frédéric (Canadian Theatre Review, 2019)
Theatre administrators, artistic directors, and heads of programs from across Canada have a conversation about how institutional policies and cultures have shifted in the wake of #MeToo. The conversation features Kristian Clarke, Executive Director of the Dancer Transition Resource Centre (DTRC); Frédéric Dubois, Director of the French Section, National Theatre School; Melanie Dreyer-Lude, Chair of the Department of Drama at the University of Alberta; Weyni Mengesha, Artistic Director of Soulpepper Theatre; Alisa Palmer, Artistic Director of the English Section, National Theatre School; Kathryn Shaw, Artistic Director of Studio 58 at Langara College; and Jacqueline Warwick, Director of the Fountain School of Performing Arts, Dalhousie University. The participants reflect on the challenges of taking stock of the impacts and effects of a cultural movement that is still unfolding and the ways in which #MeToo has changed the relationship between training institutions and the performing arts industry.
Publisher: University of Toronto Press
Keywords: #MeToo; Bibliographie; Nettoyer; Raphaël; intimacy coaching; performing arts industry; sexual harassment policy; theatre training

“Sorry Not Sorry”: Apologizing in the Wake of #MeToo - MacArthur, Michelle (Canadian Theatre Review, 2019)
This article explores what it means to apologize for misconduct in the #MeToo era through three examples from the Canadian theatre industry: a private apology (Randolph College for the Performing Arts), a public apology (Citadel Theatre), and an absent apology (Soulpepper Theatre). Understanding a public apology as a performative utterance meant to restore a community’s trust, this article suggests the importance of examining the paratexts generated by and around it that help it achieve its function. From policy revisions, to media interviews, to public forums, these materials and events are crucial in the meaning-making process in which a #MeToo apology is engaged, especially when the theatre community’s access to the apology itself is limited. The article concludes by situating its case studies in relation to issues of misconduct in theatre education and training institutions.
Keywords: #MeToo; #SorryNotSorry; Bibliographie; Canadian theatre; Citadel Theatre; Nettoyer; Randolph College for the Performing Arts; Raphaël; Soulpepper Theatre; public apologies

Mapping the Stage Differently: Theatre #MeToo Movement and Internet Culture in South Korea - Yoon, Soo Ryon (Gender IT : Feminist reflexion on Internet policie, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël

Creating Space for Gender Diverse Theatre - Meredith, John; Levine, Sloth; Gender Explosion Working Group (StageSource, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël

Preventing Sexual Harassment and Abuses of Power: A Code of Behaviour - Royal Court Theatre (2017)
Keywords: Bibliographie; Nettoyer; Raphaël

The power of abuse - Harvie, Jen (The Routledge Companion to Theatre and Politics, 2019)
Following revelations about sexual abuse in theatre and other entertainment industries in autumn 2017, this chapter explores the conditions which allow or
Keywords: Bibliographie; Nettoyer; Raphaël

Line Drawn Summit and Survey Report - Stone, Meg (Impact, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Sexual Harassment, Criminal Misconduct & Bullying in Australian Live Performance - Media Entertainment Arts Alliance (2017)
Keywords: Bibliographie; Nettoyer; Raphaël

Facing (and Fixing) the Problem of Sexual Harassment in Theatre - Lehman, Stefanie Maiya; Morris, Celestine (Southern Theatre, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Harassment and bullying in the theatre industry: a report - The Stage (The Stage, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

"for People Who Aren't Sure Who They Are, Theatre is a Great Place to Be": Narratives of Actors and their Sexual Identities - McCadden, Theodore Edward (Pennsylvania State University, 2015)
Keywords: Bibliographie; Nettoyer; Raphaël

Examining the Embodied Learning Experiences about Gender in Gay and Bisexual Male Actors - McCadden, Ted; Wright, Robin Redmon (2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Don't Act, Don't Tell: Discrimination Based on Gender Nonconformity in the Entertainment Industry and the Clinical Setting - O’Connell, Mark (Journal of Gay & Lesbian Mental Health, 2012)
The author describes anti-homosexual attitudes in the entertainment industry. Effeminate male actors generally have a hard time being cast, whether for gay or straight roles. Attitudes in the performing arts mirror those in society as a whole. Case reports are interspersed in the discussion to illustrate the points.
Publisher: Routledge _eprint: https://doi.org/10.1080/19359705.2012.658013
Keywords: Bibliographie; Nettoyer; Raphaël; acting; anti-gay; discrimination; gender nonconformity; homophobia; performing arts

Sexual Orientation & Gender Identity Diversity in Entertainment: Experiences & Perspectives of SAG-AFTRA Members - Badgett, M.V. Lee; Herman, Jody L. (SAG-AFTRA et The Williams Institute, 2013)
Keywords: Bibliographie; Nettoyer; Raphaël

Gay men in the performing arts: Performing sexualities within ‘gay-friendly’ work contexts - Rumens, Nick; Broomfield, John (Organization, 2014)
Building on emerging research on ‘gay-friendly’ organizations, this article examines if and how work contexts understood and experienced as ‘gay-friendly’ can be characterized as exhibiting a serious breakdown in heteronormativity. Taking the performing arts as a research setting, one that is often stereotyped as ‘gay-friendly’, and drawing on in-depth interview data with 20 gay male performers in the UK, this article examines how everyday activities and encounters involving drama school educators, casters and peers are shaped by heteronormative standards of gay male sexuality. Adopting a queer theory perspective and connecting with an emergent queer theory literature in organization studies, one concern articulated in this article is that heteronormative constructions of gay male sexualities constrain participants’ access to work; suggesting limits to the abilities and roles gay men possess and are able to play. Another concern is that when gay male sexualities become normalized in performing work contexts, they reinforce organizational heteronormativity and the heterosexual/homosexual binary upon which it relies. This study contributes towards theorizing the heteronormative dynamics of ‘gay-friendly’ places of work, arguing that gay male sexualities are performatively instituted according to localized heteronormativities which reinforce contextually contingent, restrictive heteronormative standards of gay male sexuality which performers are encouraged to embody and perform both professionally and personally.
Keywords: Bibliographie; Nettoyer; Raphaël

Irish Equity Survey 2016 - Irish Equity (2016)
Keywords: Bibliographie; Nettoyer; Raphaël

Facing Sexual Harassment and Abuse in the Feminizing Museum - trivedi, nikhil; Wittman, Aletheia (Journal of Museum Education, 2018)
Despite the growing number of women in museums, the undervaluing of educational work traditionally associated with women, and labor largely done by women today, persists. This begs the question: in what other ways are women and femmes working in museums undermined despite their growing presence as workers and the emerging centrality of the educational role of museums? In society more broadly, we see how undervaluing women and their labor leads to a spectrum of treatment that can be considered violent. In this spectrum, we include pay and benefit disparities, disempowerment, and marginalization through sexist, homophobic, and transphobic comments and objectification, harassment, threats, verbal, physical, emotional, and financial abuse, and at the far end of the spectrum sexual assault and murder. In this article, we discuss data collected through a survey conducted about incidences of sexual abuse and harassment experienced by museum workers. We explore the results of the survey in relation to the gender-based division of labor and skills among the museum workforce. We look to the responses to this survey as a gauge of how much power women and gender non-conforming people have in their daily work lives in museums and propose actions that could increase empowerment and support.
Keywords: Bibliographie; Myriam; Nettoyer; Sexual violence; feminization; gender equity; labor; museum education; museum workers

Politique de prévention et d’intervention contre l’intimidation, le harcèlement et la violence - École nationale de cirque - Montréal (2019)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

Politique visant à prévenir et à combattre les violences à caractère sexuel - École nationale de cirque - Montréal (2018)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

Montréal une ville festive pour toutes: Avis sur la sécurité des femmes et des jeunes femmes cisgenre et trans lors des événements extérieurs à Montréal - Conseil des Montréalaises (2017)
Keywords: Bibliographie; Camille; Nettoyer

Sexual Harassment in the Norwegian Theatre World - Kleppe, Bård; Røyseng, Sigrid (The Journal of Arts Management, Law, and Society, 2016)
The aim of this article is to provide insight into the phenomenon of sexual harassment in the theatre world. A survey among Norwegian actors is presented showing that sexual harassment is much more prevalent in the theatre world than in Norwegian work life in general. Further, the article aims at understanding why the prevalence is as high as it is. Based on qualitative interviews, the article points out some risk factors that shed light on the high prevalence of sexual harassment. Lastly, the risk factors are related to charismatic authority as an important power base in the theatre world.
Publisher: Routledge _eprint: https://doi.org/10.1080/10632921.2016.1231645
Keywords: Art organizations; Bibliographie; Nettoyer; Raphaël; charismatic authority; gender roles; mixed methods; sexual harassment; theatre

Speaking in Public: What Women Say about Working in the Video Game Industry - De Castell, Suzanne; Skardzius, Karen (Television & New Media, 2019)
Since the 1990s, conversations about the dearth of women working in the video game industry have centered on three topics: (1) ways to draw more women into the field, (2) the experiences of women working in the industry, and (3) the experiences of those who once worked in the industry but left. Although there has been considerable research on the conditions and occupational identities of video game developers, less scholarly attention has been devoted to women in gameswork, the barriers/obstacles and challenges/opportunities they face, and how they talk about their experiences. This article offers a feminist approach that demonstrates how discourse focused on affect can be reread as intimately related to silences about power and how the rhetorical constraints that public speech imposes upon what can be said about “women in games” aid us in understanding what might remain unspoken, and why.
Keywords: Bibliographie; Irina; Nettoyer

Winnipeg comedy club defends decision to book Louis C.K. despite sexual misconduct - Caruk, Holly (CBC News, 2019)
An American comedian and actor who admitted to sexual misconduct will take the stage at a Winnipeg comedy club next week but not everyone is lining up for tickets.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

ReadTheCode.ca - Canadian Creative Industries (2017)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

Pour les prochaines dénonce une culture toxique en humour - Ruel-Manseau, Audrey (La Presse, 2019)
Des humoristes de la relève affirment que le milieu de l’humour reste gangréné par la culture du viol, même deux ans après le mouvement mondial #moiaussi. En mettant sur pied Pour les prochaines, les jeunes femmes souhaitent « éradiquer » les inconduites sexuelles de l’industrie, et tendent la main aux acteurs importants du monde comique afin qu’ils s’allient pour poser des actions concrètes.
Keywords: Bibliographie; Nettoyer

Climat toxique dans le milieu de l’humour, malaises en conférence de presse - Piqueur, Lucie (Urbania, 2019)
Le regroupement « Pour les prochaines » souhaite en finir avec la culture du viol en humour, mais c'est pas gagné.
Keywords: Bibliographie; Nettoyer

The impact of intervention measures on sexual harassment in the film and television industry - Eng, Ben; McKinney, Ralph; Shao, Lawrence (Journal of International Management Studies, 2019)
Since 2017, increased sexual harassment incidents have been reported in Hollywood; yet, little guidance has been offered on how organizations, which are informally governed by their network members, can effectively reduce sexual harassment. Building upon the theory of network governance, this paper suggests social mechanisms, which are used to coordinate and safeguard exchanges between Hollywood organizations, are more effective at reducing incidents of workplace sexual harassment than traditional strategies. These social mechanisms direct change to the macroculture through collective sanctions that damage the perpetrators reputation and restrict access to network opportunities. In essence, perpetrators become toxic assets that Hollywood avoids and this avoidance is similar to economic sanctions that can deter sexual harassment.
Keywords: Bibliographie; Irina; Nettoyer

Sexual Harassment in the Creative Industries: Tolerance, Culture and the Need for Change: Sexual harassment in the creative industries - Hennekam, Sophie; Bennett, Dawn (Gender, Work & Organization, 2017)
The economic, social and cultural contributions of the creative industries are essential elements of many societies and their governments’ policies. However, there is growing evidence that precarity, competition and lack of regulation within these industries is exacerbating inequalities with respect to gender, race and class. With a focus on gender and sexual harassment among female workers, this study involved 32 in-depth interviews with women working in the Netherlands’ creative industries. Data were analyzed using content analysis. Findings suggest that sexual harassment is prevalent, and many women considered it to be part of their occupational culture and career advancement. Four factors inﬂuenced this phenomenon: competition for work; industry culture; gendered power relations; and the importance of informal networks. Implications include the need for a climate of non-tolerance, sector-speciﬁc research and guidelines, sensitivity training and further work with unions and professional associations to provide worker protection strategies traditionally undertaken by organizations. The article concludes that effective sexual harassment prevention requires action at the individual, educational, sectoral and governmental levels, beginning with public conversations to convey the message that sexual harassment is never acceptable.
Keywords: Bibliographie; Irina; Nettoyer

Gender then, gender now: surveying women's participation in Australian film and television industries - French, Lisa (Continuum : Journal of Media and Cultural Studies, 2014)
In the Australian audiovisual industries, women are a minority of the personnel in a large number of key creative roles and have considerably lower representation than in the Australian workforce generally. Despite the decline in their participation across several fields, the under-representation of women is not being addressed by these industries. Using findings from current research that includes a major survey of Victorian activity, this article engages with the urgent need for new approaches to thinking about the contribution and innovation of women: culturally, creatively and economically. Benchmarked against the last major study in 1992 (Cox and Laura), pivotal issues examined include barriers to progression, representation by job type and workplace/organizational cultures, along with a consideration of the current successes (relative to other areas) of women in television. Business, cultural and social arguments are made for the importance of gender equity, and an understanding of the contribution and value of women to these industries.
Publisher: Routledge _eprint: https://doi.org/10.1080/10304312.2014.888040
Keywords: Bibliographie; Irina; Nettoyer

Post Weinstein: gendered power and harassment in the media industries - Cobb, Shelley; Horeck, Tanya (Feminist Media Studies, 2018)
Keywords: #MeToo; Bibliographie; Irina; Nettoyer

Enquête sur le portrait sociodémographique et l’égalité homme-femme chez les créatrices et créateurs d’humour au Québec – Sommaire 2018-2: Données sur la perception de l’égalité entre les femmes et les hommes - Paré, Christelle; Brouard, François (Groupe de recherche sur l’industrie de l’humour (GRIH), SCSE/CSES, Sprott Centre for Social Enterprises / Centre Sprott pour les entreprises sociales (SCSE/CSES), Université Carleton, 2018)
Keywords: Bibliographie; Humour; Nettoyer; Sophie-Anne; Types de VACS

Resilience & Melancholy: Pop Music, Feminism, Neoliberalism - James, Robin (John Hunt Publishing, 2015)
When most people think that “little girls should be seen and not heard,” a noisy, riotous scream can be revolutionary. But that’s not the case anymore. (Cis/Het/White) Girls aren’t supposed to be virginal, passive objects, but Poly-Styrene-like sirens who scream back in spectacularly noisy and transgressive ways as they “Lean In.” Resilience is the new, neoliberal feminine ideal: real women overcome all the objectification and silencing that impeded their foremothers. Resilience discourse incites noisy damage, like screams, so that it can be recycled for a profit. It turns the crises posed by avant-garde noise, feminist critique, and black aesthetics into opportunities for strengthening the vitality of multi-racial white supremacist patriarchy (MRWaSP). Reading contemporary pop music – Lady Gaga, Beyonce, Calvin Harris – with and against political philosophers like Michel Foucault, feminists like Patricia Hill Collins, and media theorists like Steven Shaviro, /Resilience & Melancholy/ shows how resilience discourse manifests in both pop music and in feminist politics. In particular, it argues that resilient femininity is a post-feminist strategy for producing post-race white supremacy. Resilience discourse allows women to “Lean In” to MRWaSP privilege because their overcoming and leaning-in actively produce blackness as exception, as pathology, as death. The book also considers alternatives to resilience found in the work of Beyonce, Rihanna, and Atari Teenage Riot. Updating Freud, James calls these pathological, diseased iterations of resilience “melancholy.” Melancholy makes resilience unprofitable, that is, incapable of generating enough surplus value to keep MRWaSP capitalism healthy. Investing in the things that resilience discourse renders exceptional, melancholic siren songs like Rihanna’s “Diamonds” steer us off course, away from resilient “life” and into the death.
Keywords: Bibliographie; Music / History & Criticism; Nettoyer; Philosophy / Social